Movement of mitral fibrous components in an isolated porcine working heart model. (October 2015) - Tamenishi, Akinori; Araki, Yoshimori; Saito, Shunei; Oshima, Hideki; Ueda, Yuichi; Usui, Akihiko
Background: There is little research regarding the movement of mitral fibrous components. We analyzed changes in mitral fibrous components in normal and deteriorated isolated working swine hearts. Methods: In 5 swine hearts, 6 sonomicrometry transducers were placed around the mitral annulus and 2 in the papillary muscle tip. During the working cycle, we evaluated the annular dimension and calculated the contraction range and contraction ratio during the cardiac cycle in normal and deteriorated modes. Results: The transverse (24.5 ± 2.3 vs. 27.4 ± 2.4 mm) and posterior longitudinal diameter (18.3 ± 7.0 vs. 22.5 ± 5.5 mm) increased significantly in deteriorated mode. The contraction range in transverse (1.8 ± 0.6 vs. 0.8 ± 0.7 mm) and posterior longitudinal (1.6 ± 0.6 vs. 0.8 ± 0.3 mm) diameters decreased significantly in deteriorated mode. The contraction range of the strut chordae was less than 1.0 mm in both modes, with no significant differences. The contraction ratio of the anterior strut chordae was significantly reduced in deteriorated mode (3.2 ± 1.1% vs. 2.2 ± 1.1%). The contraction ratio of the annulus was significantly lower in deteriorated mode with respect to transverse (6.9 ± 2.1% vs. 2.9 ± 2.9%) and longitudinal (13.3 ± 4.5% vs. 8.6 ± 5.1%) diameters. Conclusions: In the deteriorated hearts, the mitral annulus was dilated and contractility decreased. The length of the strut chordae differed 1 mm between the deteriorated and normal modes; however, the contraction ratio of the anterior chordae during the cardiac cycle was reduced, indicating increased stretching.